Effect of the Introduction of High-speed Trains on Consumer Welfare - Ji Sun Baek (KDI Journal of Economic Policy, 2016)
This paper examines the impact of introducing high-speed trains on consumer welfare, taking the ensuing changes in train schedules into account. Based on the estimated demand model for travel which incorporates consumer's heterogeneous preferences for travel schedules into the standard discrete-choice model, I separately evaluate the impact from adding high-speed trains and that from changes in train schedules. The results indicate that consumers who travel between two cities connected by high-speed trains benefit from the introduction of high-speed trains, while some travelers whose choice set does not include high-speed trains face a reduced frequency of non-high-speed trains, resulting in significant losses.
Keywords: L13; L92; 330; Endogenous product characteristics; New product entry; Consumer surplus; Highspeed train; Korea; KTX